Determinants of Thai legal professionalism: A structural equation model analysis - Cherdsak Teeranantawanich; Thepparat Phimolsathien (My University, 2017)
The purpose of the research is to examine what constitutes professionalism amongst Thai legal practitioners and consultants.By use of simple random-sampling, the 332 legal professionals were surveyed by use of a 72-item, 7-level Likert type agreement scale questionnaire on the study's four constructs.A confirmatory factor analysis was run prior to the structural equation model, with analysis of the data undertaken by use of LISREL 9.10 software.The results showed that ethics was viewed as the most important aspect by Thai legal professionals (x̄ = 5.71), which was only slightly ahead of the legal consultant's experience (x̄ = 5.64).Opposite to this however, the legal consultants' themselves felt that client satisfaction (x̄ = 4.95), and quick solutions (x̄ = 4.84), had minimal importance.Overall results also showed that the latent variable of communications skills (0.67) was most important, followed by competency (0.33), and knowledge management (0.17).
Keywords: Legal Education and Practice Innovations